Determination of Natamycin in Fermented Dry Salami Casings - Fisera, Miroslav; Valasek, Pavel; Mlcek, Jiri; Fojtikova, Lenka; Fiserova, Lenka (Journal of food processing and preservation, 2015)
Natamycin is a natural antimicrobial food additive substance used to protect food against growth of fungi and yeast. Its use is reliable and safe for the human body. Natamycin kills fungi and yeast that could spoil the taste and smell of preserved meat products. Because of the lack of literature references on its detection in meat products, the aim of this study was to elaborate a method for determination of natamycin used to impregnate fermented dry salami casings. To detect the content of the effective substance, high‐performance liquid chromatography with UV/Vis and mass spectrometry detection was employed; natamycin had been extracted from area‐normalized surface layers of model salami protective casings to a mixture of methanol–water and detected with the above method. Moreover, the effective amount of natamycin in salami casings purchased from retail network was monitored, too. PRACTICAL APPLICATIONS: As the practical application of the above elaborated detection method, the analyses of samples of fermented dry salami casings which were purchased from a retail network showed natamycin presence just in minimal or zero amounts. Extract from area surfaces of model and real samples no contained amounts of natamycin exceeding the limits specified by valid regulations. Thus, the analyses of natamycin in casings of commercially produced fermented dry salami showed its probable ability to degrade before the salami is purchased by the consumers.